Anthropogenic disturbance has altered the habitat of two Azorean endemic coastal plants - Rúben M. Correia Rego; Mónica Moura; Maria Olangua-Corral; Guilherme Roxo; Roberto Resendes; Luís Silva (BMC Ecology and Evolution, 2024)
Abstract Background Anthropogenic threats are causing alteration of coastal areas worldwide. Most of the coastal biodiversity is endangered, taking a particular toll on island ecosystems, like the Azores. To better understand the biotic and abiotic factors constraining the distribution and conservation status of two endemic plants, Azorina vidalii (Campanulaceae) and Lotus azoricus (Fabaceae), we performed a global survey of coastal plant communities in the archipelago, also covering environmental descriptors, natural and anthropogenic threats. Moreover, we revised their IUCN conservation status and estimated the population fractions within protected areas. Results Non-indigenous plants were commonly found in plots with or without the target endemics, contributing to the absence of well-defined coastal plant communities. Nonetheless, indigenous taxa commonly occurred at the plots with L. azoricus. With a larger area of occurrence, A. vidalii ecological niche differed from that of L. azoricus, the latter being restricted to dry and rocky sea cliffs, mostly in Santa Maria Island. Besides the presence of invasive plants, signs of habitat destruction, trampling and grazing, and of natural threats, such as coastal erosion, were commonly observed. Conclusions Occurrence data indicated an endangered status for both species, although this would change to critically endangered for L. azoricus when using smaller-sized occurrence cells. Both species are threatened since their habitat is restricted to a very narrow vegetation belt, strongly limited by sea influence and human pressure, and with the frequent presence of invasive plants. While focusing on two endemic plants, our study allowed a broader view of the impact of anthropogenic disturbance on Azorean coastal plant communities.